Individual participant data meta-analysis versus aggregate data meta-analysis: a case study in eczema and food allergy prevention. - Van,Vogt E; Cro,S; Cornelius,VR; Williams,HC; Askie,LM; Phillips,R; Kelleher,MM; Boyle,RJ (Clinical and Experimental Allergy, 2021)
INTRODUCTION: Meta-analysis traditionally uses aggregate data from published reports. Individual Participant Data (IPD) meta-analysis, which obtains and synthesises participant-level data, is potentially more informative, but resource-intensive. The impact on the findings of meta-analyses using IPD in comparison to aggregate data has rarely been formally evaluated. METHODS: We conducted a secondary analysis of a Cochrane systematic review of skin care interventions for preventing eczema and food allergy in infants to identify the impact of the analytical choice on the review's findings. We used aggregate data meta-analysis only and contrasted the results against those of the originally published IPD meta-analysis. All meta-analysis used random effects inverse variance models. Certainty of evidence was evaluated using GRADE. RESULTS: The pooled treatment effects for the Cochrane systematic review's co-primary outcomes of eczema and food allergy were similar in IPD meta-analysis (eczema RR 1.03, 95% CI 0.81, 1.31; I2 41%, 7 studies 3075 participants), and aggregate meta-analysis (eczema RR 1.01 95% CI 0.77, 1.33; I2 53%, 7 studies, 3089 participants). In aggregate meta-analysis the statistical heterogeneity could not be explained but using IPD it was explained by one trial which used a different, bathing intervention. For IPD meta-analysis, risk of bias was assessed as lower and more adverse event data were available compared with aggregate meta-analysis. This resulted in higher certainty of evidence, especially for adverse events. IPD meta-analysis enabled analysis of treatment interactions by age and hereditary eczema risk; and analysis of the effect of treatment adherence using pooled complier-adjusted-causal-effect analysis, none of which was possible in aggregate meta-analysis. CONCLUSIONS: For this systematic review, IPD did not significantly change primary outcome risk ratios compared with aggregate data meta-analysis. However, certainty of evidence, safety out